Prevalence of Pap Smear among Female Health Personnel in Hospital Tuanku Ja’afar Seremban, Malaysia - Saleh, Emad Eldin; Mohamed Jamli, Mohamad; Mohamad Shahbodin, Damia; Pau, Emily; Periyathamby, Hemaprakash; Gobu, Kharpaagam; Nawinnie, Lakshika; Elhariri, Sherreen (Asian Pacific Journal of Cancer Care, 2021)
Background: Cervical cancer is the third common cancer among women in Malaysia. Human papillomavirus is most prevalent among young women with early sexual activity, multiple partners, smoking, and immunosuppression. Screening for detection and early treatment is more effective for managing cervical cancer. Papanicolaou (Pap) smear test is used for the early detection of cervical cancer. The National Health and Morbidity Survey conducted in 2019 showed only 36.6% of women in Malaysia have undertaken the test. Method: A cross-sectional study was carried out from August 2019 to October 2019 in the hospital Tuanku Ja’afar (HTJ) a tertiary government hospital in Malaysia. The target population was female healthcare personnel, the self-administered questionnaire had been used for data collection. Data analysis was done using Statistical Package for Social Science It was including socio-demographic background, lifestyle, and knowledge towards Pap smear. Our objective is to determine the incidence of Pap smears between female health personnel in the hospital. Results: The prevalence of having Pap smear done once in their life was 55.7%, only 33.5% of them had it done within the past 3 years according to the guideline. Prevalence was significantly lower in the singles, younger age, doctors, higher educational level, and higher monthly income. The main factors for poor response were a busy schedule, having no unusual symptoms, personal shyness, and fear of pain. Conclusion: The prevalence of Pap smear among female health personnel in HTJ is not consistent with their knowledge of pap smear. Hence, reinforcement of pap smear screening is important to reduce the prevalence of cervical cancer by addressing obstacles and constraints for a good response among female healthcare personnel. Moreover, awareness of screening guidelines through media, health campaigns, and health talks will help to assure practice more effectively.